Orbital forcing of ice sheets during snowball Earth - Mitchell, Ross; Gernon, T.M.; Cox, Grant; Nordsvan, Adam; Kirscher, Uwe; Xuan, C.; Liu, Yebo; Liu, X.; He, X. (NATURE PORTFOLIO, 2021)
The snowball Earth hypothesis—that a runaway ice-albedo feedback can cause global glaciation—seeks to explain low-latitude glacial deposits, as well as geological anomalies including the re-emergence of banded iron formation and “cap” carbonates. One of the most significant challenges to snowball Earth has been sedimentological cyclicity that has been taken to imply more climate dynamics than expected when the ocean is completely covered in ice. However, recent climate models suggest that as atmospheric CO2 accumulates, the snowball climate system becomes sensitive to orbital forcing. Here we show the presence of nearly all Milankovitch (orbital) cycles preserved in stratified banded iron formation deposited during the Sturtian snowball Earth. These results provide evidence for orbitally forced cyclicity of global ice sheets that resulted in periodic oxidation of ferrous iron. Orbital glacial advance and retreat cycles provide a simple mechanism to reconcile both the sedimentary dynamics and the enigmatic survival of multicellular life during snowball Earth.